2018
DOI: 10.4081/ni.2018.7638
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of neurological complications associated with Zika virus in a brazilian metropolis

Abstract: The aim of this paper is to study the prevalence of Zika Virus (ZIKV) and the index of its neurological complications. This is a quantitative, cross-sectional epidemiological study. Data were collected through the compulsory notification of suspected ZIKV and its neurological alterations cases. 113 suspected ZIKV cases were reported, most of them in the summer, with a higher prevalence of females and in the fourth decade of life. Among the neurological changes, 15 Guillain-Barré Syndrome cases were reported, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…During this review period, we included 17 case reports 46, 220– 235 , 22 case series 120, 236– 256 , seven case-control studies 4, 257262 , one ecological study 266 , one modelling study 265 and eight outbreak reports 201, 203, 206, 266270 that reported on ZIKV infection and GBS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this review period, we included 17 case reports 46, 220– 235 , 22 case series 120, 236– 256 , seven case-control studies 4, 257262 , one ecological study 266 , one modelling study 265 and eight outbreak reports 201, 203, 206, 266270 that reported on ZIKV infection and GBS.…”
Section: Resultsmentioning
confidence: 99%
“…Traveller/non-traveller populations: In studies included in this update, we found additional evidence of GBS in both travellers and non-travellers with ZIKV infection. Ten publications report on 11 travellers 218, 220, 222224, 227, 229, 232– 234 , while 34 publications report GBS due to ZIKV in 402 non travellers 4, 44, 118, 219, 221, 225, 226, 228, 230, 231, 235– 237, 239– 247, 249, 251, 253260, 262, 263 .…”
Section: Resultsmentioning
confidence: 99%